2003
DOI: 10.1023/a:1022513405603
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Our objective was to examine the diagnostic yield of duodenal aspirates for Giardia in children and compare it to results of duodenal mucosal biopsies. The results of all duodenal aspirates submitted for direct parasite examinations over a 31-month period were reviewed, as were the histological results of duodenal mucosal biopsies from these patients. In all, 161 children (89 boys; age range 0.33-18 years) were included in the study. Giardia was identified in the duodenal aspirate of 5.6% (9/161) patients and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In line with this observation, 18% of false negatives were reported in a retrospective histological analysis of duodenal samples from 567 cases of giardiasis presenting with celiac-like duodenal histology 35. In this context, the microscopic analysis of duodenal aspirate might have represented another diagnostic option, although not superior to the analysis of duodenal biopsies when available 36…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In line with this observation, 18% of false negatives were reported in a retrospective histological analysis of duodenal samples from 567 cases of giardiasis presenting with celiac-like duodenal histology 35. In this context, the microscopic analysis of duodenal aspirate might have represented another diagnostic option, although not superior to the analysis of duodenal biopsies when available 36…”
Section: Discussionmentioning
confidence: 87%
“…35 In this context, the microscopic analysis of duodenal aspirate might have represented another diagnostic option, although not superior to the analysis of duodenal biopsies when available. 36 Abdominal ultrasound with intestinal assessment showed the presence of transient small bowel intussusception that was not confirmed at CT enterography. The transient nature of small bowel intussusception was previously reported in an observational study of 25 paediatric patients, none of whom had persistent intussusception requiring surgery.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, the duodenal aspirate examination can be foregone as biopsies were found to have a better detection rate than aspirate microscopic examination [ 8 ]. In contrast, a prospective study done in 2003 showed no difference between duodenal biopsy and duodenal aspirate in detection of giardial infection; however, a recommendation of biopsy usage was made due to cost [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown superiority of duodenal aspirate samples over duodenal mucosal biopsy [43]. Others showed that duodenal mucosal biopsies were more sensitive compared to duodenal aspirate samples [44].…”
Section: Discussionmentioning
confidence: 99%